Phänomene regressiver Nachrichtenrezeption Medienethische Perspektiven auf die Konjunktur nichtrationaler mentaler Modelle der Realität - Schülke, André (Kommunikations- und Medienethik, 2023)
One phenomenon of modernity on which media ethics comments is the challenge to reason by the boom in non-rational world views. Since we are exposed to a constant stream of apocalyptic news every day, there is reason to examine news for its effect as a precursor of non-rational mental models of reality in the consciousness of its recipients. A model of cerebral information and knowledge processing by the sociologist Walter L. Bühl can be used to explain why many media users tend to align their actions with mythical, conspiracy-affiliated, anti-scientific and fundamentalist world views, thus calling into question fundamental achievements of the Enlightenment.